Blockchain and artificial intelligence - managing a secure and sustainable supply chain - Jahankhani, Hamid; Jamal, Arshad; Lawson, Shaun (Springer, 2021)
Supply chain management is often the most challenging part of any business that manufactures, sells goods, or provides services. Regardless of whether the operations are mostly physical or online, managing supply chains largely relies on being able to manage shared information securely, efficiently and effectively. Managing the information within the context of a closely-knit supply chain offers the benefits of extra resilience and ability to recover quickly from major disturbances. The authors propose here the development of a block-chain enabled and Intelligent Agent supported supply chain community that will provide a secure, intelligent, responsive and sustainable operational partnership. The technology used is simple, reasonably priced and the expected benefits considerable. The paper reports on work in progress on an enhanced prototype system.
Keywords: Blockchain; Supply chain; Intelligent Agents; Artificial Intelligence; Sustainable ecosystem